USING CRAZY STORY GAME IN TEACHING SPEAKING TO JUNIOR HIGH SCHOOL STUDENTS - Hendra Kasri; Havid Ardi (Universitas Negeri Padang, 2013)
AbstractSpeaking is one of the skills learned and practiced the first high school students in English language lessons. In this paper, the author discusses speak English teaching activities in the classroom by using Crazy Story Game. In this activity, each student wrote a card in the verb and the verb cannot show that they wrote it to other students. After that, the teacher tells the beginning of the story to the students and for students who invoked his name to continue the story using the verbs they wrote earlier. After the student had to use the verb to guess what word is write the other students. All students have the opportunity to continue the story. For students who guess the most widely used verb other students as the winner in this game. Crazy Story This game can make students speak English and make them creative in using the English language.Key words: speaking, crazy story game